Isolation and Characterization of Bacterial Contaminants from Bone Marrow-Derived Mesenchymal Stem Cell Cultures - Banu, S. Amitha; Saini, Shubham; Sharun, Khan; Mamachan, Merlin; Nair, Sonu S.; Pawde, Abhijit M.; Dhama, Kuldeep; Abualigah, Laith *; Maiti, Swapan Kumar (Journal of Pure and Applied Microbiology, 2024)
This study aimed to assess and manage bacterial contamination in multiple batches of mesenchymal stem cell (MSC) cultures derived from rabbit bone marrow. Routine visual inspection and microscopic examination were employed for the detection of the contaminated cultures. The contaminated cultures were inoculated on Nutrient agar and multiple isolated colonies were subjected to Gram staining and biochemical characterization. Further, molecular identification of the bacterial isolates was performed using polymerase chain reaction. The determination of antibiotic susceptibility patterns was conducted using the Kirby-Bauer disc diffusion method. Among the 351 mesenchymal stem cell culture (SCC) flasks monitored, only 1.42% were found to be contaminated. Based on the phenotypic and biochemical characterization, the major bacterial contaminants were identified as Staphylococcus aureus, Bacillus spp., and Escherichia coli infiltrating during various stages of cell processing. Antibiotic susceptibility patterns revealed varying responses among isolates, crucial for effective antimicrobial strategies and maintaining aseptic conditions in SCCs. The study emphasizes the importance of regular monitoring to maintain sterile environments, validate culture quality, and uphold safety standards. The findings indicate the need to establish stringent quality control measures, crucial for the successful translation of MSC research into clinical applications. The research advocates for continuous monitoring, adherence to SOPs, and further investigations into preventive strategies for ensuring the safety and efficacy of MSC-based therapies.